IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS MULTIKULTURAL DI SMK NEGERI 2 MATARAM - Nurlaili Handayani; Taat Wulandari (Universitas Negeri Yogyakarta, 2017)
AbstractThis study aimed to investigate: the implementation of multiculturalism-based character education, and the facilitating and inhibiting factors in the implementation of multiculturalism-based character education at SMK Negeri 2 Mataram. The study used the qualitative method with the naturalistic approach. They were selected by means of the purposive and snowball sampling techniques. The data were collected by, namely interviews, observations, and documentation. The data trustworthiness was enhanced by the triangulation technique. The data were analyzed by of data reduction, data display, and conclusion drawing. The results of the study are as follows. 1) The multiculturalism-based character education was implemented through the following programs: a) the school management commitment; b) the disciplined attitude building through regulations; c) the integration of intra-curricular programs; d) the integration of extracurricular programs; e) the school culture and f) network programs. School developed values such as religiosity, autonomy, care of the environment, achievement, tolerance, democracy, nationalism, competitiveness, and love of peace. 2) The facilitating factors included among others: a) good commitment and cooperation among the school principal, teachers, students, and parents’ involvement in various aspects of school activities; and b) the government and private support within the network. The inhibiting factors included among others: a) the habits and cultural environments of students’ origins which were varied; b) the social environment; c) the peer environment and electronic media; e) incomplete infrastructure facilities; and f) evaluation of program character education that had not been optimal, so that it affected the process of character inculcation.Keywords: character education, multiculturalism, multiculturalism in SMK